2016
DOI: 10.1080/02699931.2016.1244045
|View full text |Cite
|
Sign up to set email alerts
|

Motivated reasoning in the prediction of sports outcomes and the belief in the “hot hand”

Abstract: The present paper explores the role of motivation to observe a certain outcome in people's predictions, causal attributions, and beliefs about a streak of binary outcomes (basketball scoring shots). In two studies we found that positive streaks (points scored by the participants' favourite team) lead participants to predict the streak's continuation (belief in the hot hand), but negative streaks lead to predictions of its end (gambler's fallacy). More importantly, these wishful predictions are supported by str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In principle, people may notice these co-occurrences without assuming that the events are causally connected-for example, they perceive the co-occurrence as a random coincidence. In practice, however, people appear to find it hard to resist attributing co-occurrences to a proximal causal mechanism, rather than to chance (e.g., Braga, Mata, Ferreira, & Sherman, 2016;Caruso, Waytz, & Epley, 2010). As van Prooijen et al (2018), p. 321 wrote:…”
Section: Conspiracy Thinking and Perceiving Pattern And Causality In mentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, people may notice these co-occurrences without assuming that the events are causally connected-for example, they perceive the co-occurrence as a random coincidence. In practice, however, people appear to find it hard to resist attributing co-occurrences to a proximal causal mechanism, rather than to chance (e.g., Braga, Mata, Ferreira, & Sherman, 2016;Caruso, Waytz, & Epley, 2010). As van Prooijen et al (2018), p. 321 wrote:…”
Section: Conspiracy Thinking and Perceiving Pattern And Causality In mentioning
confidence: 99%
“…Each participant was presented with one scenario describing a streak of human tragedies (either the deaths of three or four journalists, or the poisoning of three or four local politicians). Streaks in events, even when they occur by chance, often trigger implausible causal perceptions such as gambler's belief in a “hot hand” (Braga et al, ; Caruso et al., ). Conspiracy explanations for the most recent of these tragedies were measured, and participants were also asked whether the events are causally connected.…”
Section: Studymentioning
confidence: 99%
“…The present work raises intriguing questions for future research. While personal relevance was absent in the present research, we suspect that motivated reasoning can guide people's attention to whichever cues support a more desired theory and evaluation (e.g., Braga, Mata, Ferreira, & Sherman, 2017). That is, the cognitive flexibility in making a judgment is open for motivational exploitation.…”
Section: Discussionmentioning
confidence: 54%
“…In the hot-hand phenomenon, a successful streak is expected to breed success (Bar-Eli, Avugos, & Raab, 2006). A success immediately before a performance is thought to have a favorable influence on the mental state or subsequent success rate, and this phenomenon has been applied, particularly in the field of sports (Braga, Mata, Ferreira, & Sherman, 2016;Shea, 2014). The majority of basketball players, coaches, and audiences believe in the existence of the hot-hand phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Raab et al (2012) showed that coaches and playmakers were sensitive to the variability in a player's performance and tended to select the players who displayed the hot-hand phenomenon for strategic decisions (e.g., allocation of the ball). The belief of hot-hand was considered to occur by strong desire of players, coaches, or audiences for winning the game (especially their favorite team) and was assumed to be related to the motivation for the game (Braga et al, 2016). In addition, the two-factor theory of emotion (Schachter & Singer, 1962) is an applicable theory that explains the process of human emotional awakening and was considered to be related to the humans' fallacious believes (Burns & Corpus, 2004).…”
Section: Introductionmentioning
confidence: 99%